Evaluation of engineering, economic and environmental suitability of waste filler incorporated asphalt mixes and pavements - Choudhary J.; Kumar B.; Gupta A. (My University, 2025)
This study investigated the engineering, economic, and environmental feasibility of asphalt mixes containing brick dust (BD), recycled concrete aggregate dust (CD), limestone slurry dust (LD), rice straw ash (RSA), glass powder (GP), carbide lime (CL), and copper tailing (CT). The performance of asphalt mixes containing various wastes was evaluated against rutting, cracking and moisture sensitivity, and their comparison was made with the conventional mix containing stone dust (SD) filler. Subsequently, the asphalt pavements utilizing the aforesaid mixes as surface course were designed and their material cost and global warming potential (GWP) were analysed. In general, the waste fillers form superior performing mixes at relatively lower cost than conventional SD fillers. The LD and RSA emerged as the best and worst performing filler, respectively. The construction of single km of asphalt pavement made with LD-incorporated mixes found to have 11% lower cost, 11% lower GWP, and 75 ton less aggregates. © 2021 Informa UK Limited, trading as Taylor & Francis Group.